Resilience Community Livelihood : Case Study on Tunda’s Island Community - Prima Yustitia Nurul Islami (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Studies on community household livelihood have been carried out mainly to explain the level of vulnerability to community livelihoods. The livelihoods of the island community are greatly influenced by natural factors and surrounding environment. The livelihoods of the island community are mostly small scale fishermen who are culnerable to climate and non climate factors. This research study explain how island communities survive with the risk of the vulnerability of their livelihood due climate change. This case study analysis was used to find out a spesific picture of community household in Tunda Island in responding to pressure and taking various adaptation measure to survive. This study has several finding to explain how community households sruve, among others by diversifying additional source of income within the household due to the main source of income that no longer produces income due to various environmental problems, one of which is climate change. The resilience of the island community is bulit through a community system that is built base on mutual awarness by using the various resources available on Tunda Island. Community resilience does not only household adaptation pattern infacing various ecological problems but also includes community adaptation patterns in maintaining the sustainability of community food system, environmental balace and household livelihood system.